Diagnostic Value of Osteopontin, Lymphocyte-to-Monocyte Ratio, and CA-125 in Ovarian Carcinoma Suspect - Surohadi, Natra D.; Triwardhani, Ria; Kustarini, Indranila; Hendrianingtyas, Meita; Rachmawati, Banundari (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
Osteopontin (OPN) is an important protein in cancer development and progressivity. Lymphocyte-to-Monocyte Ratio (LMR) as a systemic immunity and inflammatory indicator could be an ideal predictor biomarker because of its method’s simplicity and availability. Elevated CA-125 and OPN as well as decreased LMR were reported as signs of ovarian malignancy. Limited studies about OPN and LMR as diagnostic biomarkers, as well as various specificity and sensitivity of CA-125 intrigued the researcher to prove OPN, LMR, and CA-125 as diagnostic biomarkers for ovarian carcinoma. This study aimed to measure the diagnostic value of OPN, LMR, and CA-125 levels against histopathology results for ovarian carcinoma diagnosis. Eighty patients involved with suspected ovarian carcinoma who were referred to Dr. Kariadi Hospital, Semarang. Osteopontin and CA-125 levels were measured using ELISA, and LMR was calculated from absolute lymphocyte and monocyte counts using an automated hematology analyzer. The receiver operating characteristics curve was used to determine the cut-off and 2x2 table. The cut-off values for OPN, LMR, and CA-125 were 124 ng/mL, 3.7 and 45.4 U/mL, respectively. The sensitivity for OPN, LMR, and CA-125 was 67.24%, 62.07% and 60.34%. Specificity for OPN, LMR, and CA-125 were 68.18%, 54.55% and 59.09%. Osteopontin is the best parameter for determining the diagnosis of ovarian carcinoma but it is still not sufficient because OPN cut-off was still within the normal reference value.